La communication internationale à l’épreuve de la crise écologique. Contours d’un modèle de la double présence - Oumar Kane (Communiquer)
This article focuses on the rise of the environmental theme in international communication institutions and discourses. Through a content analysis of a body of theoretical work and institutional documents dating back to the 1970s, the author traces the main stages of the rise of environment as an object of concern in international communication research. It appears that development and environmental issues have emerged with a certain time lag and that the communication dimension has long remained peripheral for environmental issues while it was quickly central to development issues. Focusing on the historical mobilization of the question of “resources”, the author shows that, while it is central today for the paradigm of “sustainable development”, its genealogy is older since it has previously structured the stakes around information flows (information paradigm: C4D) and orbits and frequencies (telecommunication paradigm: ICT4D) before applying to the environmental question (ecological paradigm). The author relies on this critical genealogy of the epistemic and institutional constitution of the field of research to suggest a normative model based on an ethic of responsibility (inspired by Hans Jonas) and on two metaconditions: a horizontal principle of participation (communicative) and a principle of resilience (ecological).